Implementation of SIMADE: analysis of the performance of school principals - Lima, Carla da Conceição de (2022)
This article analyzes the implementation of the Sistema Mineiro de Administração Escolar (SIMADE) from the discretion of middle-level bureaucrats: the principals of the state public schools. Methodologically, it is a quantitative research in which it is observed: a gap between the formulation and the implementation of the policy; the production of new rules regarding the access and use of the system; implementation aimed at the administrative or pedagogical use of SIMADE. Therefore, there is a continuous work of discretion through which school principals build different policies in the context of the public state network of Minas Gerais.